Pengaruh Pengetahuan Dan Sikap Ibu Akseptor KB Tentang Alat Kontrasepsi Dalam Rahim Terhadap Pemakaian Alat Kontrasepsi Dalam Rahim Di Wilayah Puskesmas Mijen Kota Semarang - Chusnul Zulaika; Dewi Sari R.; Mirtaria K. (LPPM STIKES Guna Bangsa, 2018)
Family planning (KB) program is an effort to increase awareness and community participation through maturing marriage age (PUP), birth regulation, fostering family resilience, improving the welfare of small families, happy and prosperous. This study attempts to determine factors related to the knowledge and attitudes of family planning acceptors about uterine contraception in utero against the use of uterine contraception in the Mijen health center in Semarang. This research is a quantitative research with non experimental research design, and classified in observational survey research conducted to explain the relationship and influence between independent variables and dependent variables. The sample of this study were 60 respondents using simple random sampling. Data analysis techniques with univariate analysis, bivariate analysis by cross tabulation before statistical tests were done by Chi square test and multivariate with logistic regression analysis. The results of the study showed that the respondents of high school education (43.3%), with private employment (56.7%), distribution of IUD use (65%), the level of knowledge about the IUD was sufficient (80%) and attitudes in the use of the IUD agreed (71.67%). The bivariate results showed that there was a relationship between maternal knowledge of family planning acceptors about IUD with IUD use and there was a relationship between the attitude of mother of family planning acceptors and the use of IUD. Multivariate results show that there is an influence between knowledge and attitudes in IUD use.